Discovery of potent allosteric antibodies inhibiting EGFR - Léxane Fournier; Lukas Pekar; Birgitta Leuthner; Harald Kolmar; Lars Toleikis; Stefan Becker (mAbs)
In this work, we report the discovery of potent anti-epidermal growth factor receptor (EGFR) allosteric heavy-chain antibodies by combining camelid immunization and fluorescence-activated cell sorting (FACS). After immunization and yeast surface display library construction, allosteric clones were obtained by introducing the labeled EGF Fc fusion protein as an additional criterion for FACS. This sorting method enabled the identification of 11 heavy-chain antibodies that did not compete with the orthosteric ligand EGF for the binding to EGFR. These antibodies bind to a triple-negative breast cancer cell line expressing EGFR with affinities in the picomolar to nanomolar range. Those camelid-derived antibodies also exhibit interesting properties by modulating EGFR affinity for EGF. Moreover, they are also able to inhibit EGF-induced downstream signaling pathways. In particular, we identified one clone that is more potent than the approved blocking antibody cetuximab in inhibiting both PI3K/AKT and MAPK/ERK pathways. Our results suggest that allosteric antibodies may be potential new modalities for therapeutics.